Papers and Proceedings of the Annual Bank Conference on Development Economics : Supplement to The World Bank Economic Review - Basu, Kaushik (Published by Oxford University Press on behalf of the World Bank, 2019)
This volume contains the Papers and Proceedings of the 26th Annual Bank Conference on Development Economics (ABCDE) held on June 15–16, 2015, in Mexico City. The theme of the conference was "Productivity, Growth, and the Law," and it was hosted jointly by the Bank of Mexico and the World Bank. The 2015 ABCDE Organizing Committee was composed of Kaushik Basu (World Bank, Chair), Asli Demirguc¸-Kunt and Indermit Gill (World Bank), Alberto Torres and Laura Juarez (Bank of Mexico), and Andrew Foster (Brown University).